Creating a High-Performance Corporate Culture: A Case Study of PT Telkom Indonesia Regional 4 - Radityo Anwar Muhaimin; Arif Hartono (Cita Konsultindo Research Center, 2023)
Having highly dedicated employees who have good performance will help the company achieve its vision and mission. This study aims to discover how to create a high-performing corporate culture at PT Telkom Indonesia Regional 4. The method in this study uses a qualitative approach through case studies. The research used interview techniques with three informants from the Human Capital Unit of PT Telkom Indonesia Regional 4. The findings from this study indicate several aspects related to the company's process of building a high-performance culture, including the components of organizational culture, organizational sub-culture, high-performance culture, socialization of organizational culture, leadership attitudes towards organizational culture, and high-performance cultural systems. In implementing the process, PT Telkom Indonesia Regional 4 has challenges such as company transformation, minimal employee involvement, and diversity of backgrounds. To overcome these challenges so that creating a high-performance culture continues to run effectively, PT Telkom Indonesia Regional 4 innovates in the work environment, adjusts the culture to the workload, is adaptive, and builds personal relationships through sharing sessions with the employee union.